2020
DOI: 10.1111/clr.13631
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic outcomes and clinical performance of CAD‐CAM monolithic zirconia versus porcelain‐fused‐to‐metal implant crowns in the molar region: 1‐year results of a RCT

Abstract: Objective To investigate the clinical performance of monolithic zirconia implant crowns as compared to porcelain‐fused‐to‐metal (PFM) implant crowns. Materials and methods Seventy‐six healthy patients received reduced diameter implants in the molar region. Following random allocation, either a monolithic zirconia crown (Mono‐ZrO2) or a (PFM) was inserted. Crown and implant survival rates, modified USPHS criteria, clinical measurements, and interproximal marginal bone level (MBL) were assessed at crown delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 16 publications
5
44
0
Order By: Relevance
“…Some studies showed less patient satisfaction with monolithic zirconia when compared to bi-layered zirconia restorations, 41 while other studies reported a high satisfaction with monolithic zirconia crowns. 33,42 Color match was rated excellent in other studies investigating Enamic partial restorations. 10,43 The patients were scheduled for annual follow-up appointments and the outcome will be reported in due course.…”
Section: Discussionmentioning
confidence: 68%
“…Some studies showed less patient satisfaction with monolithic zirconia when compared to bi-layered zirconia restorations, 41 while other studies reported a high satisfaction with monolithic zirconia crowns. 33,42 Color match was rated excellent in other studies investigating Enamic partial restorations. 10,43 The patients were scheduled for annual follow-up appointments and the outcome will be reported in due course.…”
Section: Discussionmentioning
confidence: 68%
“…[4,5] The esthetic outcomes of monolithic zirconia crowns, however, were rated inferior compared to conventionally veneered restorations. [6] Therefore, custom staining and glazing of monolithic ceramic restorations is recommended to provide monolithic restorations mimicking the natural dentition. [7] The esthetic properties of dental restorations need to be maintained long-term.…”
Section: Introductionmentioning
confidence: 99%
“…These include overpressing 4) , the use of veneering indirect composite resin 5) , and employing a monolithic structure for zirconia restorations 6) . Monolithic zirconia restorations are prevalent in fixed prostheses owing to their advantages of lower frequency of porcelain chipping, preservation of the tooth structure, and low cost 7) . However, medium-and long-term clinical outcomes are still limited 2,7) .…”
Section: Introductionmentioning
confidence: 99%
“…Monolithic zirconia restorations are prevalent in fixed prostheses owing to their advantages of lower frequency of porcelain chipping, preservation of the tooth structure, and low cost 7) . However, medium-and long-term clinical outcomes are still limited 2,7) .…”
Section: Introductionmentioning
confidence: 99%